Dietary intake and health risk characterization of cadmium, lead, and mercury in milkfish (Chanos chanos) and tilapia (Oreochromis spp.) from aquaculture farms surrounding Manila bay, Philippines - Kathlene Cleah D. Benitez; Allysa Ross N. Almagro; Patrick David M. Torres; Karl Bryan S. Perelonia; Bryan E. Tanyag; Jerick Jann M. Quiambao; Ulysses M. Montojo (Regulatory Toxicology and Pharmacology, 2026)

Conceptual and Mechanistic Links between glycated hemoglobin and glycosylated RNA: An insight into glycosylation biology in metabolic disease pathophysiology - Peter Chinedu Agu; Patrick Maduabuchi Aja; Boniface Anthony Ale; Kehinde Ross; Jun Lu (Glycoconjugate Journal, 2026)

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Taphonomy of soft-tissue preservation in ferricrete at the McGraths Flat Lagerstätte - Tara Djokic; Patrick M. Smith; Jeff R. Havig; Michael Frese; Paulo Vasconcelos; Jochen Brocks; Michael Ellwood; David J. Cantrill; Dayna McGeeney; Ross Pogson; Chris Ryan; Yu Wang; et al. (Gondwana Research, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Behavioral syndromes are associated with social plasticity and competence in a wild primate - Patrick J. Tkaczynski; Liz A.D. Campbell; Ann MacLarnon; Bonaventura Majolo; Caroline Ross; Julia Lehmann (Behavioral Ecology and Sociobiology, 2025)
The ability to optimize social behavior to varying socioecological circumstances has been termed “social competence” and relies on behavioral plasticity. Behavioral syndromes, i.e. consistent individual differences in intraindividual correlations among behavioral traits, appear to be a constraint on social competence, yet studies exploring this have largely been limited to experimental laboratory settings. Here, we tested the importance of behavioral syndromes to social competence in wild Barbary macaques ( Macaca sylvanus ), an endangered primate with established links between positive social relationships and survival. We studied two groups ( n = 27 individuals) in which behavioral syndrome phenotypes were established in a previous study. Individuals with lower scores for the “excitable” phenotype (roughly equivalent to the “shy-bold” axis in other studies) showed greater plasticity compared to more “excitable” (i.e., “bolder”) individuals in affiliative responses to the immediate social environment, being more likely to initiate grooming with larger numbers of conspecific bystanders present. Less excitable individuals increased their grooming social network connectivity to a greater degree compared to more excitable individuals in periods of higher anthropogenic pressure. During colder weather, less excitable individuals concentrated their grooming network into fewer ties, whereas more excitable individuals slightly increased their number of connections. Any changes in network connectivity in relation to socioecology were small, reflecting the fact that stability in social network position is a common phenomenon in various taxa. Overall, we show that behavioral syndrome phenotypes influence plasticity in affiliative behavior and thus may be a key factor in individual responses to the rapidly changing socioecologies of the Anthropocene.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Ocean warming increases residency at summering grounds for migrating bull sharks (Carcharhinus leucas) - Nicolas Lubitz; Paul A. Butcher; Patrick Vianello; Adam Barnett; Ross G. Dwyer; Marcus Sheaves; Amy F. Smoothey (Science of The Total Environment, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Corrigendum to “9th Ishihara lecture: Effects of subsurface heterogeneity on liquefaction-induced ground deformation during earthquakes” [Soil Dynam Earthq Eng (2024), Volume 186, November 2024, 108954] - Ross W. Boulanger; Patrick Bassal (Soil Dynamics and Earthquake Engineering, 2025)

9th Ishihara lecture: Effects of subsurface heterogeneity on liquefaction-induced ground deformation during earthquakes - Ross W. Boulanger; Patrick Bassal (Soil Dynamics and Earthquake Engineering, 2024)

Toxicity evaluation of neonicotinoids to earthworm (Eisenia fetida) behaviors by a novel locomotion tracking assay - Petrus Siregar; Yu-Chen Hsieh; Gilbert Audira; Michael Edbert Suryanto; Allan Patrick Macabeo; Ross D. Vasquez; Chung-Der Hsiao (Environmental Pollution, 2024)

Mafic to intermediate volcanic rocks of the Blake River Group, Abitibi greenstone belt, Canada: Geochemistry, petrogenesis and relation with VMS deposits - Octavio Vite-Sánchez; Pierre-Simon Ross; Patrick Mercier-Langevin (Precambrian Research, 2024)

Deoxygenation following coral spawning and low-level thermal stress trigger mass coral mortality at Coral Bay, Ningaloo Reef - Zoe T. Richards; Lewis Haines; Claire Ross; Sophie Preston; Troy Matthews; Anthony Terriaca; Ethan Black; Yvette Lewis; Josh Mannolini; Patrick Dean; Vincent Middleton; Ben Saunders (Coral Reefs, 2024)
Oxygen depletion is well recognized for its role in the degradation of tropical coral reefs. Extreme acute hypoxic events that lead to localized mass mortality and the formation of ‘dead zones’ (a region where few or no organisms can survive due to a lack of oxygen) are particularly concerning as they can result in wide-ranging losses of biodiversity, ecosystem productivity and functioning, economic prosperity, and wellbeing. In March of 2022, the annual coral spawning event at Bills Bay (Coral Bay, Ningaloo Reef, Western Australia) coincided with elevated seawater temperature, calm weather conditions and a flood tide resulting in coral spawn becoming trapped in Bills Bay. Immediately after, there was a mass fish kill, which is believed to have been caused by local eutrophication resulting in severe oxygen depletion. The impact the deoxygenation and thermal stress event had on benthic communities has not yet been quantified; hence, the principal aim of this study is to document the extent of change that occurred in the benthic communities before and after the 2022 coral spawning event over a spatial gradient from the nearshore to mid-reef. Percent coral cover in the Bay decreased from 55.62 ± 2.26% in 2016–2018 and 70.44 ± 5.24% in 2021 to 1.16 ± 0.51% in 2022. Over the same period, the percent cover of turf algae increased from 27.40 ± 2.00% in 2016–2018 and 24.66 ± 6.67% in 2021 to 78.80 ± 3.06% in 2022, indicating a dramatic phase shift occurred at Bills Bay. The abundance of healthy coral colonies recorded on replicated belt transects at nine sites declined from 3452 healthy individuals in 2018 to 153 individuals in 2022 and coral generic richness decreased by 84.61%, dropping from 26 genera in 2018 to 4 genera in 2022. Previously dominant genera such as Acropora, Montipora and Echinopora, were extirpated from survey sites. Isolated colonies of massive Porite s spp. and encrusting Cyphastrea sp. survived the event and understanding the mechanisms underpinning their greater survivorship is an important area of future research. Long-term monitoring is recommended to track the community recovery process and improve our understanding of the longer-term implications of this acute mortality event on the ecological, socio-economic and cultural values of Ningaloo Reef.

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Potential role of seaweeds in climate change mitigation - Finnley W.R. Ross; Philip W. Boyd; Karen Filbee-Dexter; Kenta Watanabe; Alejandra Ortega; Dorte Krause-Jensen; Catherine Lovelock; Calvyn F.A. Sondak; Lennart T. Bach; Carlos M. Duarte; Oscar Serrano; John Beardall; et al. (Science of The Total Environment, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

An Experiential Learning Based Design Program in Rehabilitation Engineering - Sudeshna Pal; Mark Steiner; Alain J. Kassab; Patrick Pabian; Adam Golden; Edward A. Ross (Biomedical Engineering Education, 2023)

Recombinant equine FSH superovulation in the mare - Patrick M McCue; Emily M May; Brittany T Middlebrooks; Janet F Roser; Pablo J Ross; Edward L Squires (Journal of Equine Veterinary Science, 2023)

System response of an interlayered deposit with a localized graben deformation in the Northridge earthquake - Patrick C. Bassal; Ross W. Boulanger (Soil Dynamics and Earthquake Engineering, 2023)

Seaweed afforestation at large-scales exclusively for carbon sequestration: Critical assessment of risks, viability and the state of knowledge - Finnley Ross; Patrick Tarbuck; Peter I. Macreadie (Frontiers in Marine Science, 2022)
There have been discussions of scaling up offshore seaweed cultivation and sinking it exclusively for carbon sequestration (‘ocean afforestation’) and thereby help mitigate climate change, but is this concept feasible? Here we investigate the feasibility of ocean afforestation across five perspectives: 1) Ecological feasibility; 2) Technical feasibility; 3) Economic feasibility; 4) Co-benefits and risks; and 5) Governance and social considerations. Optimising ecological factors such as species selection and use of currents, alongside the use of low-cost biodegradable rafts in theory could see this concept scaled globally. An area of 400,000km 2 or 16.4 billion biodegradable rafts would be needed for 1 gigatonne of CO 2 fixation given roughly 16 rafts of 25m 2 each would be needed per tonne of CO 2 fixation. However, CO 2 fixation (calculated from net primary productivity) and carbon sequestration (carbon permanently removed from the atmosphere) are fundamentally different processes, yet this distinction is often overlooked. Quantifying carbon sequestration from ocean afforestation remains elusive given several outstanding oceanic biogeochemical considerations. For example, the displacement of phytoplankton communities and their associated carbon sequestration via nutrient reallocation is a critical knowledge gap in understanding the climate change mitigation potential of ocean afforestation. Ocean afforestation also carries complex risks to marine ecosystems, for example, the impact on benthic communities of seaweed deposition. Additionally, governance and social challenges exist such as the legality of operation in relation to ocean treaties. The concept of ocean afforestation is still in its infancy, and while there are large research gaps, further investment into research should be given before the concept can be adequately compared against the suite of potential ocean-based climate change mitigation strategies.

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

Systematic Review and Regression Modeling of the Effects of Age, Body Size, and Exercise on Cardiovascular Parameters in Healthy Adults - Aseem Pradhan; John Scaringi; Patrick Gerard; Ross Arena; Jonathan Myers; Leonard A. Kaminsky; Ethan Kung (Cardiovascular Engineering and Technology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Effect of social structure and introduction history on genetic diversity and differentiation - Sylvia M. Flucher; Patrick Krapf; Wolfgang Arthofer; Andrew V. Suarez; Ross H. Crozier; Florian M. Steiner; Birgit C. Schlick‐Steiner (Molecular Ecology, 2021)
Invasive species are a global threat to biodiversity, and understanding their history and biology is a major goal of invasion biology. Population‐genetic approaches allow insights into these features, as population structure is shaped by factors such as invasion history (number, origin and age of introductions) and life‐history traits (e.g., mating system, dispersal capability). We compared the relative importance of these factors by investigating two closely related ants, Tetramorium immigrans and Tetramorium tsushimae , that differ in their social structure and invasion history in North America. We used mitochondrial DNA sequences and microsatellite alleles to estimate the source and number of introduction events of the two species, and compared genetic structure among native and introduced populations. Genetic diversity of both species was strongly reduced in introduced populations, which also differed genetically from native populations. Genetic differentiation between ranges and the reduction in microsatellite diversity were more severe in the more recently introduced and supercolonial T . tsushimae . However, the loss of mitochondrial haplotype diversity was more pronounced in T . immigrans , which has single‐queen colonies and was introduced earlier. Tetramorium immigrans was introduced at least twice from Western Europe to North America and once independently to South America. Its monogyny might have limited genetic diversity per introduction, but new mutations and successive introductions over a long time may have added to the gene pool in the introduced range. Polygyny in T . tsushimae probably facilitated the simultaneous introduction of several queens from a Japanese population to St. Louis, USA. In addition to identifying introduction pathways, our results reveal how social structure can influence the population‐genetic consequences of founder events.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Correspondence between Breeding Values of the Same Pinus taeda L. Genotypes from Clonal Trials and Half-Sib Seedling Progeny Trials - Mohammad Nasir Shalizi; Salvador Alejandro Gezan; Steven E McKeand; Joshua R Sherrill; W Patrick Cumbie; Ross W Whetten; Fikret Isik (Forest Science, 2020)
The correspondence between breeding values of 65 loblolly pine (Pinus taeda L.) genotypes from clonal genetic tests and half-sib seedling progeny tests was studied in the southern United States. The two experiments were established separately, 10 years apart. Additive genetic variance estimates from clonal tests were larger compared with the estimates from the half-sib progeny tests, regardless of the covariance structure used in the statistical models and the traits. However, clone-mean and half-sib family-mean heritability estimates were comparable for all traits, ranging between 0.88 and 0.99. Based on the independent analysis, the correlation between the breeding values of the same genotypes from two propagule types was moderate (0.59) for tree height and stem volume. The combined analysis resulted in a strong genetic correlation (>0.93) between the breeding values of two propagule types. Herein the large discrepancy is mainly the outcome of different data analytical approaches. Conclusively, selecting genotypes for deployment based on clonal testing may not be optimal, but forest tree breeders can use the results from clonal tests to make some informed decisions.

From community-based to locally led adaptation: Evidence from Vanuatu - Ross Westoby; Karen E. McNamara; Roselyn Kumar; Patrick D. Nunn (Ambio, 2020)

Cell-Type-Specific Analysis of Molecular Pathology in Autism Identifies Common Genes and Pathways Affected Across Neocortical Regions - Dmitry Velmeshev; Marco Magistri; Emilia Maria Cristina Mazza; Patrick Lally; Nathalie Khoury; Evan Ross D’Elia; Silvio Bicciato; Mohammad Ali Faghihi (Molecular Neurobiology, 2020)

Volcanology, chemo-stratigraphy, geochronology, hydrothermal alteration and VMS potential of the Lemoine Member of the Waconichi Formation, Chibougamau district, Abitibi greenstone belt, Québec - Pierre-Simon Ross; Alexandre Boulerice; Patrick Mercier-Langevin; Vicki McNicoll (Mineralium Deposita, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The Functional Response Ratio (FRR): advancing comparative metrics for predicting the ecological impacts of invasive alien species - Ross N. Cuthbert; James W. E. Dickey; Neil E. Coughlan; Patrick W. S. Joyce; Jaimie T. A. Dick (Biological Invasions, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Geochemistry of shale and sedimentary pyrite as a proxy for gold fertility in the Selwyn basin area, Yukon - Patrick J. Sack; Ross R. Large; Daniel D. Gregory (Mineralium Deposita, 2018)

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

Minimizing opportunity costs to aquatic connectivity restoration while controlling an invasive species - Austin W. Milt; Matthew W. Diebel; Patrick J. Doran; Michael C. Ferris; Matthew Herbert; Mary L. Khoury; Allison T. Moody; Thomas M. Neeson; Jared Ross; Ted Treska; Jesse R. O'Hanley; Lisa Walter; et al. (Conservation Biology, 2018)
Controlling invasive species is critical for conservation but can have unintended consequences for native species and divert resources away from other efforts. This dilemma occurs on a grand scale in the North American Great Lakes, where dams and culverts block tributary access to habitat of desirable fish species and are a lynchpin of long‐standing efforts to limit ecological damage inflicted by the invasive, parasitic sea lamprey ( Petromyzon marinus ). Habitat restoration and sea‐lamprey control create conflicting goals for managing aging infrastructure. We used optimization to minimize opportunity costs of habitat gains for 37 desirable migratory fishes that arose from restricting sea lamprey access (0–25% increase) when selecting barriers for removal under a limited budget (US$1–105 million). Imposing limits on sea lamprey habitat reduced gains in tributary access for desirable species by 15–50% relative to an unconstrained scenario. Additional investment to offset the effect of limiting sea‐lamprey access resulted in high opportunity costs for 30 of 37 species (e.g., an additional US$20–80 million for lake sturgeon [ Acipenser fulvescens ]) and often required ≥5% increase in sea‐lamprey access to identify barrier‐removal solutions adhering to the budget and limiting access. Narrowly distributed species exhibited the highest opportunity costs but benefited more at less cost when small increases in sea‐lamprey access were allowed. Our results illustrate the value of optimization in limiting opportunity costs when balancing invasion control against restoration benefits for diverse desirable species. Such trade‐off analyses are essential to the restoration of connectivity within fragmented rivers without unleashing invaders.

Invigorating hydrological research through journal publications - Nevil Quinn; Günter Blöschl; András Bárdossy; Attilio Castellarin; Martyn Clark; Christophe Cudennec; Demetris Koutsoyiannis; Upmanu Lall; Lubomir Lichner; Juraj Parajka; Christa D. Peters-Lidard; Graham Sander; et al. (Hydrological Sciences Journal, 2018)

Geographical ecology of dry forest tree communities in the West Indies - Janet Franklin; Riley Andrade; Mark L. Daniels; Patrick Fairbairn; Maria C. Fandino; Thomas W. Gillespie; Grizelle González; Otto Gonzalez; Daniel Imbert; Valerie Kapos; Daniel L. Kelly; Humfredo Marcano‐Vega; et al. (Journal of Biogeography, 2018)
Aim Seasonally dry tropical forest ( SDTF ) of the Caribbean Islands (primarily West Indies) is floristically distinct from Neotropical SDTF in Central and South America. We evaluate whether tree species composition was associated with climatic gradients or geographical distance. Turnover (dissimilarity) in species composition of different islands or among more distant sites would suggest communities structured by speciation and dispersal limitations. A nested pattern would be consistent with a steep resource gradient. Correlation of species composition with climatic variation would suggest communities structured by broad‐scale environmental filtering. Location The West Indies (The Bahamas, Cuba, Hispaniola, Jamaica, Puerto Rico, US Virgin Islands, Guadeloupe, Martinique, St. Lucia), Providencia (Colombia), south Florida ( USA ) and Florida Keys ( USA ). Taxon Seed plants—woody taxa (primarily trees). Methods We compiled 572 plots from 23 surveys conducted between 1969 and 2016. Hierarchical clustering of species in plots, and indicator species analysis for the resulting groups of sites, identified geographical patterns of turnover in species composition. Nonparametric analysis of variance, applied to principal components of bioclimatic variables, determined the degree of covariation in climate with location. Nestedness versus turnover in species composition was evaluated using beta diversity partitioning. Generalized dissimilarity modelling partitioned the effect of climate versus geographical distance on species composition. Results Despite a set of commonly occurring species, SDTF tree community composition was distinct among islands and was characterized by spatial turnover on climatic gradients that covaried with geographical gradients. Greater Antillean islands were characterized by endemic indicator species. Northern subtropical areas supported distinct, rather than nested, SDTF communities in spite of low levels of endemism. Main conclusions The SDTF species composition was correlated with climatic variation. SDTF on large Greater Antillean islands (Hispaniola, Jamaica and Cuba) was characterized by endemic species, consistent with their geological history and the biogeography of plant lineages. These results suggest that both environmental filtering and speciation shape Caribbean SDTF tree communities.

Secular distribution of highly metalliferous black shales corresponds with peaks in past atmosphere oxygenation - Sean C. Johnson; Ross R. Large; Raymond M. Coveney; Karen D. Kelley; John F. Slack; Jeffrey A. Steadman; Daniel D. Gregory; Patrick J. Sack; Sebastien Meffre (Mineralium Deposita, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Felsic maar-diatreme volcanoes: a review - Pierre-Simon Ross; Gerardo Carrasco Núñez; Patrick Hayman (Bulletin of Volcanology, 2017)

Connexin Hemichannels: Methods for Dye Uptake and Leakage - Ross G. Johnson; Hung C. Le; Kristen Evenson; Shelby W. Loberg; Tori M. Myslajek; Andrea Prabhu; Ann-Marie Manley; Colette O’Shea; Haiying Grunenwald; Madelaine Haddican; Patrick M. Fitzgerald; Timothy Robinson; et al. (The Journal of Membrane Biology, 2016)

Expression of the retinoic acid catabolic enzyme CYP26B1 in the human brain to maintain signaling homeostasis - Patrick N. Stoney; Yara D. Fragoso; Reem Bu Saeed; Anna Ashton; Timothy Goodman; Claire Simons; Mohamed S. Gomaa; Angelo Sementilli; Leonardo Sementilli; Alexander W. Ross; Peter J. Morgan; Peter J. McCaffery (Brain Structure and Function, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Kumdykolite, kokchetavite, and cristobalite crystallized in nanogranites from felsic granulites, Orlica-Snieznik Dome (Bohemian Massif): not evidence for ultrahigh-pressure conditions - Silvio Ferrero; Martin A. Ziemann; Ross J. Angel; Patrick J. O’Brien; Bernd Wunder (Contributions to Mineralogy and Petrology, 2016)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Real-Time Observations of the February 2010 Chile and March 2011 Japan Tsunamis Recorded in Honolulu by the Pacific Islands Ocean Observing System - Julia Fiedler; Margaret McManus; Michael Tomlinson; Eric De Carlo; Geno Pawlak; Grieg Steward; Olivia Nigro; Ross Timmerman; Patrick Drupp; Chris Ostrander (Oceanography, 2014)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

An in‐field experimental test of pinniped behavioral types - Sean D. Twiss; Ross Culloch; Patrick P. Pomeroy (Marine Mammal Science, 2012)
There has been extensive recent interest in the concepts of behavioral types, behavioral syndromes, and personalities in nonhuman animal species. Evidence for behavioral types now exists from a wide range of taxa, from mollusks to mammals. However, marine mammals are poorly represented in this literature. Here, we describe an in‐field experimental test of behavioral types in breeding gray seals, using a remotely controlled vehicle to deliver a standardized test stimulus to target individuals. We report on the design and implementation of this test and on the behavioral responses of individuals. Analysis of behavioral responses from both males and females revealed consistent individual differences across tests, suggesting that this is a practical and viable technique for determining individual variation in behavioral type in the field. Despite extensive literature on behavioral types, studies of behavioral types in wild populations remain rare. It is, therefore, important to develop ways to identify and quantify the existence of behavioral types in natural populations, because only by doing this, can we hope to ascertain the ecological and evolutionary relevance of behavioral types.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Biodegradable Implants for Sustained Drug Release in the Eye - Susan S. Lee; Patrick Hughes; Aron D. Ross; Michael R. Robinson (Pharmaceutical Research, 2010)

Linkage disequilibrium mapping in the Newfoundland population: a re-evaluation of the refinement of the Bardet?Biedl syndrome 1 critical interval - Yanli Fan; Jane S. Green; Alison J. Ross; Philip L. Beales; Patrick S. Parfrey; William S. Davidson (Human Genetics, 2005)

A bovine whole-genome radiation hybrid panel and outline map - John L. Williams; André Eggen; Luca Ferretti; Christine J. Farr; Mathieu Gautier; Giuseppe Amati; Glynn Ball; Tiziana Caramorr; Ricky Critcher; Sandro Costa; Patrick Hextall; David Hills; et al. (Mammalian Genome, 2002)

Identification of missense, nonsense, and deletion mutations in the GRHPR gene in patients with primary hyperoxaluria type II (PH2) - Kylie E. Webster; Patrick M. Ferree; Ross P. Holmes; Scott D. Cramer (Human Genetics, 2000)

Stimuli influencing mating behavior in the garter snake, Thamnophis radix - Patrick Ross; David Crews (Behavioral Ecology and Sociobiology, 1978)